PARENTING PARENTS RELATED TO THE DURATION OF GADGET USING IN PRESCHOOL AGE CHILDREN - Jayantika, Oktiya Rani; PH, Livana; Indrayati, Novi (Jurnal Ners Widya Husada, 2020)
Gadgets are media that are used as modern communication tools and make communication between humans easier. Impacts that occur Negative impacts in using gadgets can damage the eye health, addiction and even the quality of sleep will be reduced. The purpose of this study was to determine the relationship of parenting parents with the duration of the use of gadgets in preschool children. This type of research uses descriptive correlation. Research design this uses a cross sectional approach. The sampling technique used is random sampling. The sample in this study were 138 respondents. Data analysis was performed on Chi-Square requirements. The results of this study shows the majority of parents have permissive parenting with an average duration of use of the gadget for 1 hour as many as 43 respondents (31, 2%). The results of the research analysis obtained p-value of 0,000 this value is smaller than p <0.05 so it can be concluded that there is a relationship between parenting parents with the duration of the use of gadgets in preschool children. Parental care is very influential in preschoolers in the use of gadgets. For nursing, especially mental and community nursing to provide health education, especially preschoolers who are addicted to gadgets to be able to reduce the impact that will occur on their health.